Expressed Emotion, Alcohol Use Disorder Tendency and The Moderating Role of Congruence Among Unemployed Young Adult Males - Autriz, Arianne Espiritu; Cadayona, Joshua Querido; Dominguez, Jemerson; Mercano, Joelan (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2024)
Alcohol use disorder (AUD) is an emerging concern in the Philippines as its numbers continue to increase, hence, identifying risk factors of AUD is a necessity. Throughout the years, the contributing factor of the familial environment in the form of expressed emotion (EE) was associated with relapse of various psychological disorders including AUD. However, a scarcity of local literature investigating the aforementioned variable is evident. This study was conducted to elucidate the relationship of expressed emotion, congruence, and the risk of having AUD, and the moderating role of congruence among unemployed young adult males. This research utilized a cross-sectional, explanatory research design (n = 52) in which the relationship of the variables was analyzed through partial correlation and moderation analysis. Following data analysis, EE has a weak positive relationship with AUD tendency. It was also ascertained that congruence and EE have a moderate inverse relationship. However, no significant relationship was found between AUD tendency and congruence. Furthermore, it was revealed that congruence does not moderate the strength and degree of the relationship between EE and AUD tendency. Low-risk alcohol consumption must be maintained, and congruence must be sustained to regulate EE at a minimal level. Their families are encouraged to persist in their positive relationships with them, as these would likely boost their self-acceptance and contain the risk of developing AUD. Regulating the drinking habits is recommended as the family’s negative interactions towards the person would be least likely to occur. Keywords: expressed emotion; alcohol use disorder tendency; congruence